Inventory Management with Asset-Based Financing - Buzacott, John A.; Zhang, Rachel Q. (Management Science, 2004)
Most of the traditional models in production and inventory control ignore the financial states of an organization and can lead to infeasible practices in real systems. This paper is the first attempt to incorporate asset-based financing into production decisions. Instead of setting a known, exogenously determined budgetary constraint as most existing models suggest, we model the available cash in each period as a function of assets and liabilities that may be updated periodically according to the dynamics of the production activities. Furthermore, our models allow different interest rates on cash balance and outstanding loans, which is an enhancement over most traditional models in that inventory financed by a loan may be more expensive than that by out-of-pocket cash. We demonstrate the importance of joint consideration of production and financing decisions in a start-up setting in which the ability to grow the firm is mainly constrained by its limited capital and dependence on bank financing. We then explain the motivation for asset-based financing by examining the decision making at a bank and a set of retailers in a newsvendor setting.